If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 72 + -5x = 13x + 20 Reorder the terms: 72 + -5x = 20 + 13x Solving 72 + -5x = 20 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 72 + -5x + -13x = 20 + 13x + -13x Combine like terms: -5x + -13x = -18x 72 + -18x = 20 + 13x + -13x Combine like terms: 13x + -13x = 0 72 + -18x = 20 + 0 72 + -18x = 20 Add '-72' to each side of the equation. 72 + -72 + -18x = 20 + -72 Combine like terms: 72 + -72 = 0 0 + -18x = 20 + -72 -18x = 20 + -72 Combine like terms: 20 + -72 = -52 -18x = -52 Divide each side by '-18'. x = 2.888888889 Simplifying x = 2.888888889
| 6+5n=9-2n | | 0.07x*0.03=0.38 | | 1.4(a+6)=2.8(a+10) | | -97-8x=60-22x | | 112=1.5s | | 6x(2x+7)= | | 9+3(-7y+1)=6(y+7)+6 | | 50+65+x=505 | | 4x-3=7x+18 | | 6x(2x-7)= | | 9x=14x-21 | | -7x+11=19-x | | 3+10n=12n-3 | | 0-5x=6x+19 | | (y/4)=-10 | | g(x)=x^2-2X+5 | | x^3+3sinx+2cosx=2 | | 85-6x=w | | 2-5y=18 | | 3x-7+4=28 | | 2432+42= | | 5x+2+4x=7+2x-4 | | 2432+4= | | 2(3x+2)-4(3x-1)=-4 | | 4x^2-5x+9=7x+4 | | 20w^2-9w=0 | | 3(3x+4)=5(-x+2) | | 4x^2-23x+22=-6x+4 | | b^2-11b+28=0 | | 2mx-4=5x+3m | | 4(x+2)=2x-3x-7 | | 3.649.12.3v=146.329 |